Effect of training on postural control in figure skaters: A randomized controlled trial of neuromuscular versus basic off-ice training programs - Kovacs, E. J.; Birmingham, T. B.; Forwell, L.; Litchfield, R. B. (Clinical Journal of Sport Medicine, 2004)
Objectives: To compare the effect of a neuromuscular training program and a basic exercise program on postural control in figure skaters. Design: Two groups; parallel design; prospective, randomized controlled trial. Setting: Postural control laboratory, arenas, September 2001 to December 2002. Participants: Forty-four young, healthy figure skaters (18 years +/- 3 years). Interventions: Participants were randomly assigned to receive a neuromuscular training program (n = 22) or a basic exercise training program (n = 22). Both programs were completed 3 times per week for 4 weeks, and each session was supervised. Main Outcome Measurements: Participants completed baseline and postintervention measures of postural control on a force plate. Postural control was quantified as the center of pressure (CoP) path length during tests of single-limb standing balance that mimicked figure skating skills and challenged the postural control system to varying degrees. The primary outcome measure was the CoP path length observed during a landing jump test completed with eyes closed. Results: The post intervention CoP path lengths during the more challenging tests were significantly (P < 0.05) lower (indicating better postural control) for the neuromuscular trained group than for the basic exercise-trained group. For the landing jump test completed with eyes closed, the percent improvement in the neuromuscular trained group was significantly greater (mean = 21.0 +/- 22.0%) than the basic exercise trained group (mean = -4.9 +/- 24.9%; P < 0.05). The magnitude of improvement in the neuromuscular-trained group ranged from approximately 1% to 21%, depending on the specific postural control test used. Conclusions: The results suggest that off-ice neuromuscular training can significantly improve postural control in figure skaters, whereas basic exercise training does not.